Does the Temperature of the Distension Medium Affect Pain Perception in Patients undergoing Ambulatory Hysteroscopy? - Sai Kalmegh; Meenal Patvekar (Journal of Clinical and Diagnostic Research)
Introduction: Ambulatory Hysteroscopy (AH) has become a valuable tool for modern gynaecologists. However, its success largely depends on the patient’s perception of pain. Advances such as the vaginoscopic technique and the use of smaller instruments have significantly reduced discomfort. Additionally, the use of warm saline as the distension medium is thought to further alleviate pain. Aim: To compare the degree of pain perceived by patients undergoing office hysteroscopy using normal saline as a distension medium at room temperature with that using normal saline warmed to 37.5°C. Materials and Methods: A prospective interventional study was conducted at the Department of Obstetrics and Gynaecology, Dr. D. Y. Patil Medical College Hospital and Research Centre, Pimpri, Pune, Maharashtra, India from August 2022 to August 2024. AH was performed on 60 patients using the vaginoscopic technique. Patients were randomly classified into two groups of 30 each. Group A used room temperature normal saline as a distension medium, while Group B used normal saline warmed to 37.5°C. After 15 minutes of the procedure, patients from both groups were asked to rate their level of discomfort throughout the procedure on a 10-cm Visual Analogue Scale (VAS), and the pain scores were compared. The Chi-square test was utilised to determine the association between two independent categorical variables. Results: The age of the women ranged from 34 to 53 years, with a mean age of 41.77±6.28 years. Among the 60 patients, 40 (66.67%) were premenopausal, and 20 (33.33%) were menopausal. The most common indication was Abnormal Uterine Bleeding (AUB) in 17 (28.3%) patients. Mild pain (0-3) was reported by 15 women in Group A and 24 women in Group B (p-value=0.041). Moderate pain was experienced by 10 women in Group A and 6 in Group B. Severe pain was reported by 5 patients in Group A and none in Group B. Conclusion: The use of warm saline in AH is a simple, easy and cost-effective method for reducing pain and optimising clinical outcomes.